E-waste recycling intention paradigm of small and medium electronics store managers in Bangladesh: An S–O–R perspective. Issue 12 (December 2020) - Mahmud, Imran; Sultana, Sadia; Rahman, Ashikur; Ramayah, T.; Cheng Ling, Tan
Each year Bangladesh produces around 400, 000 metric tonnes of e-waste. E-waste accumulation is expected to increase by 20% annually. In order to facilitate e-waste recycling, it is crucial to identify the factors. In this study, building on the stimulus-organism-response framework, we develop a research model to explore the effect of information publicity, ascription of responsibility and convenience of recycling on the recycling attitude, subjective norm, personal norm and perceived behaviour control which lead to recycling intention. Data were gathered from 127 small and medium electronics store managers. The structural equation modelling technique was used to test the paths. The result suggests a significant influence of the element of stimulus (S) on the element of organism (O). The relationship between the element of organism (O) and the element of response (R) is partial. This paper contributes to the body of work dedicated to helping us better understand the recycling behaviour from the stimulus-organism-response perspective. From the viewpoint of practice, this research sheds light on some of the challenges that the implementer might face when making strategy and policy for e-waste management in Bangladesh.